Brazilian consensus for diagnosis, management and treatment of transthyretin familial amyloid polyneuropathy - Pinto, Marcus Vinicius; Barreira, Amilton Antunes; Bulle, Acary Souza; Freitas, Marcos Raimundo Gomes de; França, Marcondes Cavalcante, Jr; Gondim, Francisco de Assis Aquino; Marrone, Carlo Domenico; Marques, Wilson, Jr; Nascimento, Osvaldo J. M.; Rotta, Francisco Tellechea; Pupe, Camila; Waddington-Cruz, Márcia (Arquivos de Neuro-Psiquiatria, 2018)
Transthyretin familial amyloid polyneuropathy is an autosomal dominant inherited sensorimotor and autonomic polyneuropathy, which if untreated, leads to death in approximately 10 years. In Brazil, liver transplant and tafamidis are the only disease-modifying treatments available. This review consists of a consensus for the diagnosis, management and treatment for transthyretin familial amyloid polyneuropathy from the Peripheral Neuropathy Scientific Department of the Brazilian Academy of Neurology. The first and last authors produced a draft summarizing the main views on the subject and emailed the text to 10 other specialists. Relevant literature on this subject was reviewed by each participant and used for the individual review of the whole text. Each participant was expected to review the text and send a feedback review by e-mail. Thereafter, the 12 panelists got together at the city of Fortaleza, discussed the controversial points, and reached a consensus for the final text.
Keywords: amyloid neuropathies, familial; polyneuropathies